Early assessment: Trial plot study of leucaena lueucocephala / Wan Mohd Nazri Wan Abdul Rahman …[et al.] - Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Ab Rahman, Hilmi; Japarudin, Yani; Anuar, Azhar; Pailing, Mustapha (2010)
Forest plantations also provide additional non-wood forest products and benefit, from the trees planted or from other elements of ecosystem such as environmental, social and economic benefits. Fast growing and high yielding tree plantations are becoming an important source of wood in tropical countries. Leucaena leucocephala is widely used as a shade tree because of its fast growth (lead tree) compared to the other commercial tropical tree. Base on daily observations in nursery, a positive growth rates for both of tree height and tree diameter. The result shows that Leucaena has the potential to become a super fast growing forest plantation species. However, from the early study it is shown that it is prone to sagging if planted far apart.